MILITARY COOPERATION OF THE JEWISH POPULATION OF GALICIA WITH THE WEST UKRAINIAN PEOPLE'S REPUBLIC (1918–1923) - STETSYSHYN, Oleh (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2024)
Abstract. This article examines a little-known topic of both Ukrainian history and European history - the participation of the Jewish population of Eastern Galicia (now – the western part of Ukraine) in the development and combat operations of the Galician Army (Ukrainska Halyts'ka armiia, UHА), which was created in 1918 by the authorities of the West Ukrainian People's Republic (Zakhidno Ukrainska Narodna Respublika, ZUNR). It also discusses the attitude of Galician Jews towards the emergence of the Ukrainian state and the armed confrontation between Ukrainians and Poles for control of this territory. The article draws on archival documents, memories, and research to clarify the reasons for the appearance of Jewish soldiers in the Ukrainian army, discuss the most famous Jewish service members of the UHA, and analyse the post-war fate of many Jewish militaries of the Ukrainian army. These facts are little known to researchers of the history of Central-Eastern Europe and have not yet been introduced into scientific circulation.